PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR - Suci Debiati; Muftihatul Khoiriyah; Anggraeni, Anggi; Farhurohman, Oman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to understand the contribution of teachers in enhancing students’ learning motivation at the elementary school level. Learning motivation is a crucial element that affects students’ success in achieving learning objectives. In addition to functioning as instructors, teachers also have strategic roles as motivators, facilitators, mentors, and classroom managers in creating an effective and enjoyable learning environment. This study employs a literature review method, which involves examining various sources such as books, academic journals, and previous studies related to this topic. Data collection is carried out through searching, classifying, and analyzing written sources relevant to the role of teachers and student motivation. The findings of this study indicate that the role of teachers has a significant impact on improving students’ learning motivation. Teachers can provide support, use varied teaching methods, and create a positive learning environment, which can enhance students’ interest, participation, and enthusiasm for learning. Therefore, optimizing the role of teachers is essential in improving students’ learning motivation in elementary schools through appropriate and innovative teaching strategies